Relationship between risk factor control and vascular events in the SAMMPRIS trial. (24th January 2017) - Turan, Tanya N.; Nizam, Azhar; Lynn, Michael J.; Egan, Brent M.; Le, Ngoc-Anh; Lopes-Virella, Maria F.; Hermayer, Kathie L.; Harrell, Jamie; Derdeyn, Colin P.; Fiorella, David; Janis, L. Scott; Lane, Bethany; et al.
Abstract : Objective: The Stenting and Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) study is the first stroke prevention trial to include protocol-driven intensive management of multiple risk factors. In this prespecified analysis, we aimed to investigate the relationship between risk factor control during follow-up and outcome of patients in the medical arm of SAMMPRIS. Methods: Data from SAMMPRIS participants in the medical arm (n = 227) were analyzed. Risk factors were recorded at baseline, 30 days, 4 months, and then every 4 months for a mean follow-up of 32 months. For each patient, values for all risk factor measures were averaged and dichotomized as in or out of target. Results: Participants who were out of target for systolic blood pressure and physical activity, as well as those with higher mean low-density lipoprotein cholesterol and non–high-density lipoprotein, were more likely to have a recurrent vascular event (stroke, myocardial infarction, or vascular death) at 3 years compared to those who had good risk factor control. In the multivariable analysis, greater physical activity decreased the likelihood of a recurrent stroke, myocardial infarction, or vascular death (odds ratio 0.6, confidence interval 0.4–0.8). Conclusions: Raised blood pressure, cholesterol, and physical inactivity should be aggressively treated in patients with intracranial atherosclerosis to prevent future vascular events. Physical activity, which has not received attention in stroke prevention trials, was the strongest predictor of a good outcome in the medical arm in SAMMPRIS. ClinicalTrials.gov identifier: NCT00576693.